Effect of dietary Ca:P ratio on ionized calcium and calcium homeostasis in cats with early-stage chronic kidney disease - Jean A. Hall; Leslie B. Hancock; Elizabeth M. Morris (PLoS ONE, 2026)
The aim of the study was to compare two renal foods with different Ca:P ratios on manifestation of hypercalcemia and regulation of calcium homeostasis in cats with chronic kidney disease (CKD). Nine cats (11.0 ± 2.0 y) with naturally-occurring IRIS Stage I or II CKD were fed a senior wellness food for 28-days, then randomized into two groups and fed either a food providing 1.8 g/Mcal Ca, 1.3 g/Mcal P, and Ca:P ratio of 1.4:1 (MOD-Ca:P), or a food providing 2.4 g/Mcal Ca, 1.3 g/Mcal P, and Ca:P ratio of 1.8:1 (HIGH-Ca:P) for 56 days. After a 28-day washout period, cats were crossed over to the other test food. Blood and urine samples were collected at the end of the prefeed/washout and on days 28 and 56 of each study period. Data were analyzed using a linear mixed model with fixed effects of Diet, Day, Period and associated interactions. At baseline, mean ionized calcium (iCa; 1.26 ± 0.03 mmol/L) was within the normal reference interval (1.10–1.40 mmol/L). Serum total Ca, phosphorus, calcitriol, and fractional excretion of calcium were not affected by diet and diet by day interaction ( P > 0.050). There was a trend for increased fibroblast growth factor 23 ( P = 0.058) and serum iCa ( P = 0.067) in cats fed HIGH-Ca:P compared with MOD-Ca:P food, although iCa remained within the normal reference interval. Parathyroid hormone was reduced when cats were fed HIGH-Ca:P compared with cats fed MOD-Ca:P ( P = 0.020), although concentrations were within the normal reference interval throughout the study. Fractional excretion of phosphorus was reduced when cats were fed HIGH-Ca:P compared with MOD-Ca:P ( P = 0.050). Serum Cr and SDMA were higher on days 28 and 56 compared with baseline ( P < 0.002). Higher dietary Ca and a higher Ca:P ratio may not be the sole drivers of hypercalcemia in cats with progressive CKD. However, the observed alterations in calcium homeostatic mechanisms warrant further research to identify strategies for mitigating hypercalcemia risk.